Skrining SGOT dan SGPT sebagai Deteksi Dini Gangguan Fungsi Hati untuk Peningkatan Kualitas Hidup - Sidarta, Erick; Santoso, Alexander Halim; Wijaya, Bryan Anna; Fajarivaldi, Kresna Bambang; Bachri, Fiqi Afrizal (Journal of Community Service and Society Empowerment, 2026)
Liver disease is a major contributor to global morbidity and mortality, with its burden increasing due to epidemiological transition and lifestyle-related risk factors. A key challenge is the lack of early detection, as many cases are identified only at advanced stages when treatment becomes less effective. This community engagement program aimed to perform liver function screening through SGOT and SGPT measurements as a promotive–preventive strategy to enhance community health. Conducted at Asisi Church, South Jakarta, the program involved 99 elderly participants (mean age 71.85 years) who received education on liver disease risk factors and underwent biochemical assessment. The mean SGOT level was 26.17 U/L and SGPT 22.59 U/L, with no participants exhibiting elevated transaminases. These findings indicate a low prevalence of abnormal liver enzyme levels, though interpretation should consider possible healthy volunteer effects and age-related changes. The program highlights the value of integrating simple biochemical screening with health education to improve awareness and support early prevention of liver disease in community settings.